"I Should Know Better": The Roles of Relationships, Spirituality, Disclosure, Stigma, and Shame for Older Women Living With HIV Seeking Support in the South. (January 2015) - Grodensky, Catherine A.; Golin, Carol E.; Jones, Chaunetta; Mamo, Meheret; Dennis, Alexis C.; Abernethy, Melinda G.; Patterson, Kristine B.
Abstract : N/A: The population of older people living with HIV in the United States is growing. Little is known about specific challenges older HIV‐infected women face in coping with the disease and its attendant stressors. To understand these issues for older women, we conducted semi‐structured in‐depth interviews with 15 women (13 African American, 2 Caucasian) 50 years of age and older (range 50–79 years) in HIV care in the southeastern United States, and coded transcripts for salient themes. Many women felt isolated and inhibited from seeking social connection due to reluctance to disclose their HIV status, which they viewed as more shameful at their older ages. Those receiving social support did so mainly through relationships with family and friends, rather than romantic relationships. Spirituality provided great support for all participants, although fear of disclosure led several to restrict connections with a church community. Community‐level stigma‐reduction programs may help older HIV‐infected women receive support.